Ultrathin Screen‐Printed Plant Wearable Capacitive Sensors for Environmental Monitoring - Elliot J. Strand; Anupam Gopalakrishnan; Catherine A. Crichton; Mallory J. Palizzi; Owen Lee; Tomoko Borsa; Eloise Bihar; Payton Goodrich; Ana Claudia Arias; Sean E. Shaheen; Robert R. McLeod; Gregory L. Whiting (Advanced Sensor Research)
Abstract Printable and wearable plant sensors offer an approach for collecting critical environmental data at high spatial resolution to understand plant conditions and aid land management practices. Here, screen printed capacitive devices that can measure relative humidity (RH) directly at the plant‐environment interface, are demonstrated in an ultra‐thin (<6 µm) form factor. Using screen printing and a temporary tattoo transfer process, a simple technique is established to: 1) enclose printed electronic features between two layers of ethyl cellulose (EtC), 2) mount printed microparticle carbon‐based electronics onto a variety of plant structures, and 3) dramatically increase the capacitance and sensitivity for humidity sensors when compared to unencapsulated devices. This sandwich tattoo capacitor (STC) platform exhibits an RH sensitivity up to 1000 pF/%RH and stability while mounted to living plant leaves over several days. Electrochemical impedance spectroscopy (EIS) validates the formation of electric double layers within the EtC films that encapsulate the printed electrodes providing tunable capacitance values based on the ionic concentration of the device transfer fluid.